2007
DOI: 10.1186/1471-2261-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Home-based exercise rehabilitation in addition to specialist heart failure nurse care: design, rationale and recruitment to the Birmingham Rehabilitation Uptake Maximisation study for patients with congestive heart failure (BRUM-CHF): a randomised controlled trial

Abstract: Background: Exercise has been shown to be beneficial for selected patients with heart failure, but questions remain over its effectiveness, cost-effectiveness and uptake in a real world setting. This paper describes the design, rationale and recruitment for a randomised controlled trial that will explore the effectiveness and uptake of a predominantly home-based exercise rehabilitation programme, as well as its cost-effectiveness and patient acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…A recent systematic review reported no significant difference in total mortality between home or centre-based CR within 3–12 months of follow-up 19. Jolly et al extended these findings to 24 months after CR 31. Additionally, in the present study cardiac mortality was 2.1%, which is similar to other published reports of CR participants 29 30.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent systematic review reported no significant difference in total mortality between home or centre-based CR within 3–12 months of follow-up 19. Jolly et al extended these findings to 24 months after CR 31. Additionally, in the present study cardiac mortality was 2.1%, which is similar to other published reports of CR participants 29 30.…”
Section: Discussionsupporting
confidence: 89%
“…Of these, 5.1% were hospitalised for myocardial infarction. Contrary to this finding, Dalal et al 32 and Jolly et al 31 reported no significant differences in cardiac events between home and centre-based CR during up to 24 months of follow-up. The length of follow-up or the level of comorbidity among the patient populations may account for these differences.…”
Section: Discussionmentioning
confidence: 75%
“…Less than half of the eligible patients wished to participate. Similar findings were recently reported from a British study in which only 169 of 1 639 patients followed in a CHF clinic could be included in a home based training study (25). Extending inclusion criteria to patients with heart failure with preserved LVEF would have resulted in more eligible patients, but since the bulk of evidence on exercise training is based on patients with systolic heart failure and the group of patients with non-systolic heart failure is less well defined, this was beyond the scope of this study.…”
Section: Discussionsupporting
confidence: 84%
“…The patients with CF experience several symptoms, many of which are non-specific and frequently result in reduction of the functional capacity and in worsening of the quality of life (QL), both related to dyspnea and fatigue during the daily activities 5,6 .…”
Section: Introductionmentioning
confidence: 99%